EFFECTS OF MAGNESIUM FERTILIZATION ON RICE YIELD, MAGNESIUM AND POTASSIUM UPTAKE BY RICE AT VARIABLE APPLIED POTASSIUM LEVELS (Biological Sciences - PJSIR, 2002)
A  greenhouse  experiment  was conducted  at University  Putra  Malaysia  to evaluate  the effects  of magnesium  (Mg)  fertilization on rice yield , Mg and potassium (K) uptake by rice at variable applied potassium levels . Two soils (Guar and Hutan series), three Mg rates (0, 10 and 20 kg Mg ha- 1    and three K rates (0, 20 and 40 kg 1(,0 ha- 1    were used  in the study.  Grain)                                                                                                        )and straw yields, total Mg and total K uptakes were significantly higher in  Guar  series compared  to Hutan  series. Potas  sium effect was not significant on any of the  parameters.  Magnesium  fertilization  increased  grain  and  straw yields, Mg  and K uptakes significantly in both  the  soils. Regression  analysis indicated  that estimated  grain and  straw yield  responses to added Mg were linear in nature in Guar series while these were quadratic in nature in Hutan series. Similar trends were  found  for total Mg and K  uptakes.  The findings of this study indicate that Mg fertilization      should  be done in Mg deficientsoils to  increase  rice yield.